Avaliação de estratégias prejudiciais aos interesses dos stakeholders - Braga, Edilson Santos (2023)
Studies focusing on public organizations have given significant prominence to stakeholder theory, since it constitutes an important theoretical framework with regard to the relationship between public administration and stakeholders. Public organizations have multiple interests and stakeholders that must be taken into account in the decision-making process by public managers. This fact is accentuated when one considers that stakeholder theory has defended a positive view of stakeholder strategies, and paid little attention to those considered negative, harmful or unethical to them. In view of this, the general objective of this study is to evaluate and explore organizational actions considered harmful to stakeholders. To this end, the following specific objectives were established: to identify in the literature which dimensions make up stakeholder strategy; to assess the perception of the stakeholders of a HEI in relation to harmful strategies; to empirically test the proposed framework among groups of stakeholders. The research was carried out at a public university and its stakeholders were the population, i.e. students, permanent staff and outsourced workers. The data was collected using a Likert-type questionnaire, which was constructed based on the following dimensions: i) Damage directed at the stakeholder; ii) Magnitude and severity of the damage; iii) Optional damage; iv) Violation of organizational values; v) Violation of ethical principles; vi) Damage to a stakeholder with no power of choice. The data was analyzed and processed using statistical software, the Statistical Package for the Social Science - SPSS, in which descriptive statistics and Exploratory Factor Analysis tests were carried out. The main results show that stakeholders' perception of how harmful or unethical a strategy is is related to various factors, such as: which group the actions are aimed at and what their impact is; the type of strategy the institution adopts depending on the influence a particular group has; the openness to dialogue conditioned by the influence of each group; the emotional and material damage the institution's actions cause to stakeholders, among others. It was also evident that, in general, the perception of the stakeholders in this study in relation to the actions of the institution surveyed is not bad, but still needs improvement, as most of the participants' answers were concentrated in the do not agree options. In the neither agree nor disagree option and in the agree option. Furthermore, looking at the two factors generated from the statistical analysis, it can be seen that the averages of both are around 3, with the average for factor 1 being 2.95 and the average for factor 1 being 2.89. For the literature, this study contributes to the identification of two dimensions and for the university by showing that its actions still need to be improved in order to serve its stakeholders, so it is important that the university seeks to engage in more dialogue with its stakeholders, considering the aspirations and needs of each group